Effects of Species Introduction on Aquatic Communities - Santoul, Frédéric; Boulêtreau, Stéphanie (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Freshwater ecosystems are deeply affected by human pressure, such as species introduction, which remains a major concern for these ecosystems. The arrival of new species can have different ecological effects, and sometimes leads to biological invasions and adverse impacts. Introduced species establish new interactions (e.g., predation, competition) with the recipient community. These can modify the aquatic community's structure, composition, and functions. Understanding these interactions remains a key concern in conservation biology. This Special Issue of Water aims to explore these topics.